Information technology investment analysis of hospitality using information economics approach - Eva Novianti; Ahmad Nurul Fajar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This study aims to determine the feasibility of IT investment in hospitality and determine the value and tangible/ intangible benefits from IT implementation. Problem arises from high investment without knowing the real impact and future investment to IT development. The scope of this research is information technology investment in five star hotel in Jakarta. The data were collected by distributing questionnaires to the research samples, are Grand Hyatt Hotel, Mandarin Oriental Hotel and Ayana Midplaza Hotel Jakarta. The analysis uses the information economics (IE) approach that combines financially and non-financial calculations to determine the feasibility of IT investment and the benefits of IT for 5-star hotels in Jakarta. From the analysis result, it can be concluded that five star hotel in Jakarta is feasible to make IT investment with ROI score more than 1 and scorecard value 28 which shows that IT investment in 5-star hotel is quite beneficial for hotel business process.